A munkabérfizetés és munkabérvédelem alapvető kérdései a magyar munkajogi szabályozásban és joggyakorlatban - Kristóf, Nóra (Debreceni Jogi Műhely, 2018)
The aim of my publication is to scrutinise the Hungarian rules concerning the protection of wages and concluding how effectively they serve the social interests of employees. Furthermore, I researched if the regulation is efficient and consistent enough to protect the employees in point of the compensation for work.During the research, I was examining the efficiency of the protection of the employees and their salaries in practice. The other question was whether the current regulation is satisfactory enough to provide the main purposes. In order to answer these questions I was analysing the theoretical dimension and the judicial practice as well.I concluded that even if there are some incompleteness and inconsistency in the Hungarian labour law, the regulation seems appropriate and rational concerning the interests of the employees. In my opinion, the social function of labour law serves the employees’ interests enough to give them a decent standard of living.